THE EFFECTIVENESS OF DISCOVERY LEARNING MODEL TO IMPROVE ELEMENTARY STUDENTS’ CRITICAL THINKING SKILLS AND SELF EFFICACY - Ana Mufidatus Sa’adah; Haryono; Tri Joko Raharjo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The learning model is a means used to implement plans for achieving the learning objectives, one of which is social science learning subjects. In the 21st century, students are required to have critical thinking skills. Critical thinking is a way of thinking to analyze problems. In increasing critical thinking skills, the students must learn independently through discovery learning and based on self-efficacy. Through the discovery learning model, the student’s critical thinking skills and self-efficacy will increase. The purpose of the research is to determine the effectiveness of the discovery learning model to improve students' critical thinking skills and self-efficacy. The research uses quasi-experimental. In total, 48 students participated in the research with 26 participating in the experimental class and 22 participating in the control class. Data collection methods include tests, non-tests questionnaires, and note-taking. Data analysis using descriptive analysis, prerequisite tests, and hypothesis testing (including the N-Gain and mean difference tests) were to check the data. The N-Gain TKBK values are 1.7903 for the experimental group and the control group. The experimental group's N-Gain self-efficacy score are compared to the control group, and the NGain value is 1.4253. Through a higher effectiveness value than 1, it is clear that the discovery learning model is effective to increaxse students’ critical thinking skills and self-efficacy.